Persistence Of King George VI To Overcome His Stutter In The King's Speech Movie (2010) Directed By Tom Hooper: A Psychoanalytic Approach - Handayani, Eka Wahyu (2012)
This research investigated how is persistence of King George VI to overcome his stutter reflected in The King's Speech movie (2010) directed by Tom Hooper, especially viewed from psychoanalytic approach. The objectives of the research are to analyze the film based on its structural element and to analyze the film based on the psychoanalytic approach. The research paper belongs to the qualitative research. The object of the study is the persistence of King George VI to overcome his stutter reflected in The King's Speech movie. The data source comes from primary data source that is The King's Speech movie and secondary data sources are related to the movie. The method of data analysis used in this study is descriptive analysis. The study shows the following conclusions. Firstly, the structural elements of the movie present a good unity because it has related one to another. Tom Hooper extends the theme of this movie is about the persistence to reach goals and desires of life. Secondly, based on psychoanalytic analysis this movie reflects King George VI's persistence to overcome his stutter.